ANALYSIS OF NURSING CARE THROUGH WOUND CARE FOR POST-OP CA MAMMAE PATIENTS WITH NURSING PROBLEMS AT INFECTION RISK AMONG POST-OP CA MAMMAE PATIENTS IN ROOM G1 RSPAL DR. RAMELAN SURABAYA - Djumati, Sarmi; Hasina, Siti Nur; Winoto, Priyo Mukti Pribadi; Afiyah, R. Khairiyatul (Nurse and Holistic Care, 2024)
Introduction: Ca Mammae postoperative patients experience wounds susceptible to infection if not treated properly. Objective: This study aims to analyze nursing care through wound care for Post Op Ca Mammae patients with nursing problems at infection risk for Post Op Ca Mammae patients in Room G1 RSPAL Dr. Ramelan Surabaya. Methods: The research design of this final scientific work uses the case method, with the subject being one patient with nursing problems and a risk of infection with a medical diagnosis of Ca Mammae. The research was conducted in Room G1 RSPAL Dr. Ramelan Surabaya for six days, using data collection methods including comprehensive assessment, diagnosis, intervention, implementation, and evaluation. Results: The results of a case study on Ca Mammae with nursing problems of infection risk show that being given nursing care therapy with wound care can reduce the risk of infection so that the client looks fitter, the wound is covered with sterile gauze, the bleeding stops, the wound edges start to dry on the 7th day, the pain scale 3, no signs of redness, body temperature 36.3 0C, no swelling around the surgical wound, reduced odor, the middle wound is still wet and requires further care at home Conclusions: Wound care can reduce infection risk in post-op Ca Mammae patients. Nurses are expected to be able to continue applying wound care to other clients who have the risk of infection problems and educate the public about post-cancer wound care while at home.